Living supramolecular polymerization of an amphiphilic aza-BODIPY dye realized by water-assisted kinetic trapping. Issue 55 (21st June 2022) - Liu, Yan; Pan, Hongfei; Yuan, Siyuan; Ding, Jiahui; Jiang, Yuanyuan; Ren, Xiang-Kui; Chen, Zhijian
Abstract : A kinetic-controlled aggregation pathway of amphiphilic aza-BODIPY 1 was established by using H2 O as a co-solvent in MeOH and living supramolecular polymerization was realized for this dye. Abstract : The kinetic assembly pathways of a newly synthesized amphiphilic aza-BODIPY dye 1 were tuned by using H2 O as a co-solvent in MeOH. Accordingly, the biphasic aggregation pathways resulting in kinetically-trapped and thermodynamically stable aggregates of 1 were established and the multiple cyclic seeded living supramolecular polymerization of this dye was realized.